Charles Valentine Riley : founder of modern entomology - Sorensen, Willis Conner (The University of Alabama Press, 2018)
"This definitive biography is the first full account of a fascinating American scientist whose leadership created the modern science of entomology that recognizes both the essential role of insects in natural systems and their challenge to the agricultural food supply that sustains humankind. Charles Valentine Riley: Founder of Modern Entomology tells the story of how Riley (1843-1895), a young British immigrant to America--with classical schooling, only a smattering of natural history knowledge, and with talent in art and writing but no formal training in science--came to play a key role in the reorientation of entomology from the collection and arrangement of specimens to a scientific approach to insect evolution, diversity, ecology, and applied management of insect pests."--